Why Do Consumers Buy Organic? Exploring Motivations and Socio-Economic Patterns - Dominika Jakubowska; Małgorzata Grzywińska-Rąpca; Mariola Grzybowska-Brzezińska (Agriculture)
The study explored the relationship between motivations and attitudes for purchasing certified organic food and the socio-economic characteristics of consumers. The research involved 1020 Polish respondents, using in-depth interviews with a structured electronic questionnaire. Participants were selected through non-random, purposive sampling, selecting only consumers of organic food. The findings revealed that altruistic-egoistic motives are prevalent among consumers with higher food expenditure, particularly on organic products. Three main categories of organic food consumers’ attitudes were identified: pro-environmental, driven by concerns for sustainability and environmental protection; pro-health, centered on personal and family health and food safety; and pro-wellbeing, focusing on personal satisfaction, emotional wellbeing, and ethical considerations. Women were more likely to prioritize pro-health attitudes, reflecting a focus on personal and family health. Additionally, higher household income was linked to stronger pro-environmental and pro-health purchasing attitudes. This study contributes to consumer behavior theory and practical applications by offering a framework that integrates altruistic-egoistic and hedonic motives, as well as pro-environmental, pro-health, and hedonic attitudes, illustrating their roles in shaping organic food purchasing decisions and highlighting the interplay between these motivations and socio-economic characteristics.